Gastrokine 2 Regulates the Antitumor Effect of JAK2/STAT3 Pathway in Gastric Cancer. (2nd August 2021) - Zhou, Yu; Xu, Shan; Liu, Jiao; Zhu, Yaping; Zhu, Yaxin; Li, Wei; Ling, Hui
Abstract : GKN2 (gastrokine 2) mainly plays a regulatory role in gastric mucosal defense and cell protection mechanisms, and its role in gastric cancer has not been thoroughly elucidated. Immunohistochemistry was used to detect GKN2 and TFF1 expressions in 90 gastric cancer tissues, 48 neoplastic resection margins, and 22 normal gastric mucosa epithelia. It showed that the downregulation of GKN2 and TFF1 expressions in gastric cancer tissues was significantly different from that in adjacent normal gastric tissues and distal gastric mucosal tissues. Nevertheless, correlation analysis showed that GKN2 expression in gastric cancer tissues was independent of TFF1 expression. After overexpression of GKN2 was constructed in human gastric cancer cell line MKN28 with the Ad-GFP-GKN2 transfected, cell viability was measured by CCK-8 assay, and migration and invasion ability were analyzed by transwell migration assay and transwell invasion assay. It indicated that overexpression of GKN2 significantly reduced the viability of MKN28 and SGC7901 cells. Overexpression of GKN2 could also inhibit the migration and invasion ability in MKN28 and SGC7901 cells. In addition, upregulation of GKN2 can inactivate the JAK2/STAT3 pathway. Our data suggest that GKN2 and TFF1 play the antitumor role in gastric carcinoma, and TFF1 may not interact or cooperate with GKN2. GKN2 overexpression can inhibit the growth and metastasis by downregulating the JAK2/STAT3 pathway in gastric cancer cells.